ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF NEONATAL SEPSIS IN NEONATAL INTENSIVE CARE UNIT - Waseem, Hafsa; Sadaf, Rabia; Khan, Abdul Jalil; Naeem, Afnan; Ali, Sakhawat; Usman, Javaid (Annals of Allied Health Sciences, 2022)
Objective: To determine the antimicrobial susceptibility pattern of neonatal sepsis in the neonatal intensive care unit. Material & Methods: A cross-sectional study was conducted from January to July 2018 at the department of microbiology, Army medical college Rawalpindi. Blood and MacConkey agar were used for colony identification and pigment production, Gram stain was done to identify Gram-positive and Gram-negative bacteria, Rapid tests like catalase, coagulase, motility, and oxidase were performed, and API 10S and 20 E were used to identify at genus and species level. For sensitivity testing of antimicrobials modified Kirby- Bauer Disk Diffusion method was used. Data was analyzed in SPSS. Results: Out of the total of 470 samples 137(29%) were positive. Gram-positive were 43(31.3%) and Gram-negative were 94(68.6%). Maximum organisms were Stenotrophomonas maltophilia and Serratia marscenes which were 26 (19%) each followed by Klebsiella pneumoniae 18 (13.1%) and others. Pathogens showed 100% resistance to ampicillin and were maximum sensitive to colistin. However, Gram-positive were 100% sensitive to minocycline and linezolid and Gram-negative showed maximum sensitivity towards tigycycline which is 75.4%. Conclusion: Minocycline or linezolid in combination with tigycycline is the drug of choice for the management of neonatal sepsis.